2015
DOI: 10.5713/ajas.15.0185
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soyabean Isoflavones Exposure on Onset of Puberty, Serum Hormone Concentration and Gene Expression in Hypothalamus, Pituitary Gland and Ovary of Female Bama Miniature Pigs

Abstract: This study was to investigate the effect of soyabean isoflavones (SIF) on onset of puberty, serum hormone concentration, and gene expression in hypothalamus, pituitary and ovary of female Bama miniature pigs. Fifty five, 35-days old pigs were randomly assigned into 5 treatment groups consisting of 11 pigs per treatment. Results showed that dietary supplementation of varying dosage (0, 250, 500, and 1,250 mg/kg) of SIF induced puberty delay of the pigs with the age of puberty of pigs fed basal diet supplemented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The soybean ISF-supplemented pigs also showed a reduction in ovary of steroidogenic acute regulatory protein and KiSS-1 metastasis-suppressor. To conclude, soybean ISF adversely affected the reproduction sys-tem in female pigs by delaying the onset of puberty due to the decreased expression in reproduction-regulating genes [133].…”
Section: Pigsmentioning
confidence: 86%
See 1 more Smart Citation
“…The soybean ISF-supplemented pigs also showed a reduction in ovary of steroidogenic acute regulatory protein and KiSS-1 metastasis-suppressor. To conclude, soybean ISF adversely affected the reproduction sys-tem in female pigs by delaying the onset of puberty due to the decreased expression in reproduction-regulating genes [133].…”
Section: Pigsmentioning
confidence: 86%
“…Similar to the Chinese mini-pig boars, another study also investigated the effects of soybean ISF on the onset of puberty, serum hormone concentration, and gene expression in hypothalamus, pituitary gland and ovary of female Bama miniature pigs [133]. The pigs received dietary soybean ISF doses between 0 and 1250 mg/kg.…”
Section: Pigsmentioning
confidence: 99%
“…Dietary genistein has been reported to cause a persistent estrus phase, lowered serum progesterone and inhibited the development of CL (Awoniyi et al, 1998; Seppen, 2012). Genistein also inhibits the steroidogenic enzymes, steroidogenic acute regulatory protein, CYP11A1, and hydroxysteroid dehydrogenases 3B1, which play an important role in progesterone synthesis (Fan et al, 2015). Our meta‐analysis revealed that genistein decreased the number of corpora lutea in dams; however, progesterone levels remained unaffected.…”
Section: Discussionmentioning
confidence: 99%
“…It alters the intracellular levels of calcium ions in sperm cells (García-Galiano et al, 2012). While the Kiss1 gene is mainly regulated by endogenous sex steroids (Fan et al, 2015), some exogenous phytochemicals may alter the level of Kiss1 gene expression, induce hormonal changes, and affect puberty (Okafor et al, 2014;2020a). Here, we studied the changes in the Kiss1 gene expression in the blood and the testis of adult Animal procurement, Care and Handling Fifteen (15) male Wistar rats were procured from the animal housing facility of the College of Health Sciences, Nnamdi Azikiwe University and acclimatized for two (2) weeks (to rule out any intercurrent infection) under standard housing condition (ventilated room with o-12/12hour light/dark cycle at 24±2 o C).…”
Section: Introductionmentioning
confidence: 99%
“…It alters the intracellular levels of calcium ions in sperm cells ( García-Galiano et al ., 2012 ). While the Kiss1 gene is mainly regulated by endogenous sex steroids ( Fan et al ., 2015 ), some exogenous phytochemicals may alter the level of Kiss1 gene expression, induce hormonal changes, and affect puberty ( Okafor et al ., 2014 ; 2020a ). Here, we studied the changes in the Kiss1 gene expression in the blood and the testis of adult male Wistar rats following the administration of methanolic extract of MEHS.…”
Section: Introductionmentioning
confidence: 99%